The melodramatic public : film form and spectatorship in Indian cinema - Vasudevan, Ravi (Permanent Black, 2010)
"What does it mean to say Indian movies are melodramatic? How do film audiences engage with socio-political issues? What role has cinema played in the emergence of new economic forms, consumer cultures, and digital technologies in a globalizing India? The Melodramatic Public analyzes melodrama as a narrative architecture and expressive form which connect the public and the private, the personal and the political, in ways that draw film audiences into complex passages of historical change. Vasudevan explores film form and narrative strategy across a wide repertoire of film traditions, including popular classics and canonical art works. Topics include the contemporary global moment associated with the category "Bollywood," changes in state policy and industrial organization, and the impact of digital technologies, new economies of consumption, and wider export markets on Indian film culture" --